(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Since the middle of the ХХ century, the rapid spread of exotic species and their successful penetration in natural and artificial ecosystems has led to significant environmental changes all over the world [1, 2]. As it was pointed out by many researchers, biological invasion by alien species is one of the main threats to biodiversity [3, 4, 5, 6, 7]. Gmelinoides fasciatus (Stebbing 1899) attracts special attention due to the fact that it is the most successful alien species among other invaders in aquatic ecosystems in Eurasia. This invasive amphipod of Baikalian origin was first recorded in Lake Onego in 2001 by Berezina and Panov [8]. The results of the present study indicate that the invader significantly expanded its areal in Lake Onego during the last 15 years. At present amphipod G. fasciatus is dominant on the biomass among macrozoobenthos community in littoral biotopes of some islands and east part of the Lake. In Lake Onego the invader has a one-year life cycle with the generations of the previous and current year. Seasonal dynamics of the amphipod abundance in Lake Onego has two peaks during the vegetation period. According to our data G. fasciatus successfully reproduces in the new environment and shows stable sexual structure with sex ratio of approximately 1:1. Female fecundity of the amphipod in the Lake varied from 3 to 22 eggs per female, the average variation of fertility is 9 eggs per female. Revealed data of G. fasciatus abundance and biomass in Lake Onego are comparable with those for other water bodies where this amphipod species was successfully established earlier.